Improving Attendance at Post–Emergency Department Follow‐up Via Automated Text Message Appointment Reminders: A Randomized Controlled Trial. (11th November 2014) - Arora, Sanjay; Burner, Elizabeth; Terp, Sophie; Nok Lam, Chun; Nercisian, Aren; Bhatt, Vivek; Menchine, Michael; Gratton, Matthew C.
Abstract Objectives Patients discharged from the emergency department (ED) are often referred for primary care, specialty, or other disease‐specific follow‐up appointments. Attendance at these scheduled follow‐up appointments has been found to improve patient outcomes, decrease ED bounce‐backs, and reduce malpractice risk. Reasons for missing follow‐up visits are complex, but the most commonly reason cited by patients is simply forgetting. In this study the authors evaluated the ability of an automated text message reminder system to increase attendance at post‐ED discharge follow‐up appointments in a predominantly Hispanic safety‐net population. Methods This was a randomized controlled trial of ED patients with outpatient follow‐up visits scheduled at the time of ED discharge. A total of 374 English‐ and Spanish‐speaking patients with text‐capable mobile phones were enrolled. Patients in the intervention arm received automated, personalized text message appointment reminders including date, time, and clinic location at 7, 3, and 1 day before scheduled visits. A t‐test of proportions was used to compare outcomes between intervention and control groups. Both an intention‐to‐treat (ITT) and a per‐protocol analysis of the data were performed. The ITT more accurately reflects real‐world conditions where errors such as number entry errors are bound to occur. The per‐protocol analysis adds value by isolating the effect of the intervention by comparing patients who actually received it compared with those who did not. Results In the per‐protocol analysis of the primary outcome, the overall appointment adherence rate was 72.6% in the intervention group compared with 62.1% in the control group (difference between groups = 10.5%, 95% confidence interval [CI] = 0.3% to 20.8%; p = 0.045; number needed to treat = 9.5). In the ITT analysis, the overall appointment attendance rate 70.2% in the intervention group compared with 62.1% in the control group (difference between groups = 8.2%; 95% CI = –1.6% to 17.7%; p = 0.100). In a secondary largely exploratory analysis, the intervention was found to have the most benefit in patients with the lowest baseline follow‐up rate (English speakers with specialty care appointments). Conclusions Automated text message appointment reminders resulted in improvement in attendance at scheduled post‐ED discharge outpatient follow‐up visits and represent a low‐cost and highly scalable solution to increase attendance at post‐ED follow‐up appointments, which should be further explored in larger sample sizes and diverse patient populations.